Managing the development of digital marketplaces in Asia - Asian Development Bank; Villafuerte, James; Yap, Josef; Park, Cyn-Young (Manila,Philippines Asian Development Bank, 2021)
The coronavirus disease (COVID-19) pandemic is accelerating digital transformation across Asia and the Pacific. Digital platforms have become prominent intermediaries or marketplaces that allow the exchange of goods, services, and information. They are opening new transaction channels while lowering service costs and enhancing market efficiency. This volume explores topics that include trade and e-commerce, fintech payments, the digital divide, promoting competition, the digitalization of work and the role of universal basic income, and international taxation.
Introduction and Overview - - Measuring the Platform Economy: Concepts, Indicators, and Issues - - Digital Platforms, Technology, and Their Macroeconomic Impact - - Trade and E-Commerce in Asia: Policy Considerations - - Retail Fintech Payments: Facts, Benefits, Challenges, and Policies - - Digital Divide and the Platform Economy: Looking for the Connection from the Asian Experience - - Promoting Competition in the Digital Platform Economy - - Digitalization of Work and the Role of Universal Basic Income in Developing Asia - - Digital Platforms and International Taxation in Asia.
Keywords: Finance sector development; Governance and public sector management; Industry and trade -- Covid-19,disease; Information and Communications Technology; Social development and protection; Economics